2006
DOI: 10.1002/bp060274b
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Mineralized Nodule Formation in Living Osteoblastic Cultures Using Fluorescent Dyes

Abstract: Detecting the formation of mineralized nodules in osteogenic cell culture provides a means of assessing mature osteoblast cell function and the status of culture. In the present study, to continuously monitor the formation of mineralized nodules during the entire culture period, different concentrations of two fluorescent dyes (xylenol orange and calcein blue) were evaluated for their ability to specifically label calcified areas and their toxicity to cells in osteogenic cultures. Results showed that 20 microM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(115 citation statements)
references
References 15 publications
(9 reference statements)
2
108
0
Order By: Relevance
“…5). Day 7 analyses reflected minimal HA deposition, because mineralization processes typically peak after 2 weeks in culture [28,60,68,70]. …”
Section: Resultsmentioning
confidence: 99%
“…5). Day 7 analyses reflected minimal HA deposition, because mineralization processes typically peak after 2 weeks in culture [28,60,68,70]. …”
Section: Resultsmentioning
confidence: 99%
“…Fixed samples were processed into cryoblocks, and nondecalcified sections (5 lm) were obtained to qualitatively observe repair, the mineral deposition pattern visualized by bone labels, and alkaline phosphatase (AP) staining for osteoblastic activity [21,22,41,44]. Slides were imaged at 9 5 magnification and high-resolution image mosaics were acquired.…”
Section: Vital Bone Labelsmentioning
confidence: 99%
“…These time periods were selected because previous studies showed that a great increase in the calcium content was observed during in vitro cell cultures between 12 to 21 days. 46 CPC disks with hESCd-MSCs cultured in the osteogenic medium were fixed with 10% formaldehyde and stained with Alizarin Red S (ARS; Millipore, Billerica, MA), which stained calcium-rich deposits by cells into a red color. An osteogenesis assay (Millipore) was used to extract the stained minerals and measure the ARS concentration, following the manufacturer's instructions.…”
Section: Mineral Synthesis By Hescd-mscsmentioning
confidence: 99%